"Remand" in the Light of Ghulam Sarwar Case: Judgement Passed by Lahore High Court with Respect to Recommendations of Charges, Its Legality and Scope Under Code of Conduct, 2016 (Journal of Social Sciences Review, 2023)
Lord Hewart said that justice must not only be done but must also be seen to be done. Keeping in view the very spirit of this dictum, it is fair enough to say that each and every block of the legal system must be carefully placed following the principles of law so that no one is condemned with abusive power. Fair trial, due process of law, and all such principles enlisted in the framework of a legal system make it effective, efficient, and just.
Keywords: Remand; Justice; Courts; Prosecutors; Police